Alterations of voltage‐dependent K+ channels in the mesenteric artery during the early and chronic phases of diabetes. (September 2016) - Hong, Da Hye; Li, Hongliang; Kim, Hye Won; Kim, Han Sol; Son, Youn Kyoung; Yang, Se‐Ran; Park, Jeong‐Ran; Ha, Kwon‐Soo; Han, Eun‐Taek; Hong, Seok‐Ho; Firth, Amy L.; Na, Sung Hun; et al.
Summary: This study investigated the alteration of voltage‐dependent K + (Kv) channels in mesenteric arterial smooth muscle cells from control (Long‐Evans Tokushima Otsuka [LETO]) and diabetic (Otsuka Long‐Evans Tokushima Fatty [OLETF]) rats during the early and chronic phases of diabetes. We demonstrated alterations in the mesenteric Kv channels during the early and chronic phase of diabetes using the patch‐clamp technique, the arterial tone measurement system, and RT‐PCR in Long‐Evans Tokushima (LETO; for control) and Otsuka Long‐Evans Tokushima Fatty (OLETF; for diabetes) type 2 diabetic model rats. In the early phase of diabetes, the amplitude of mesenteric Kv currents induced by depolarizing pulses was greater in OLETF rats than in LETO rats. The contractile response of the mesenteric artery induced by the Kv inhibitor, 4‐aminopyridine (4‐AP), was also greater in OLETF rats. The expression of most Kv subtypes‐ including Kv1.1, Kv1.2, Kv1.4, Kv1.5, Kv1.6, Kv2.1, Kv3.2, Kv4.1, Kv4.3, Kv5.1, Kv6.2, Kv8.1, Kv9.3, and Kv10.1‐were increased in mesenteric arterial smooth muscle from OLETF rats compared with LETO rats. However, in the chronic phase of diabetes, the Kv current amplitude did not differ between LETO and OLETF rats. In addition, the 4‐AP‐induced contractile response of the mesenteric artery and the expression of Kv subtypes did not differ between the two groups. The increased Kv current amplitude and Kv channel‐related contractile response were attributable to the increase in Kv channel expression during the early phase of diabetes. The increased Kv current amplitude and Kv channel‐related contractile response were reversed during the chronic phase of diabetes.